1985
DOI: 10.1126/science.227.4683.125
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Fluorescence and Bonding of Metal Dimers

Abstract: This article describes a technique for the spectroscopic of metal clusters and intermetallic compounds. First, metallic samples are vaporized by a pulsed YAG (yttrium-aluminum garnet) laser, and then the gaseous products are excited with a pulsed-dye laser until they fluoresce. A time-resolved, fluorescence spectrum is then measured by the product. The application of this technique to the study of metal dimers is reviewed, with emphasis on recent results from Be(2) and Cr(2). Studies of such species often yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 55 publications
2
32
0
1
Order By: Relevance
“…The potential energy curve of the ground state of Be2 has been the subject of a number of theoretical investigations (14)(15)(16)(17)(18) but in spite of the large number of calculations with various degrees of sophistication, it was only recently that reliable calculations on the potential energy curve for the ground state of Be2 have Feen reporte$ (14,16,17). The calculated values of Re = 2.51 A (16), 2.50A (17) and D, = 2.23-2.34kcal/mol (14), 2.04 k 0.2kcal/mol (17) are in good agreement with the experimentally determined values of Re = 2.465 A, and D, = 2.29 kcal/mol (24)(25)(26).…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…The potential energy curve of the ground state of Be2 has been the subject of a number of theoretical investigations (14)(15)(16)(17)(18) but in spite of the large number of calculations with various degrees of sophistication, it was only recently that reliable calculations on the potential energy curve for the ground state of Be2 have Feen reporte$ (14,16,17). The calculated values of Re = 2.51 A (16), 2.50A (17) and D, = 2.23-2.34kcal/mol (14), 2.04 k 0.2kcal/mol (17) are in good agreement with the experimentally determined values of Re = 2.465 A, and D, = 2.29 kcal/mol (24)(25)(26).…”
Section: Introductionsupporting
confidence: 76%
“…Electronic excitation by promoting one electron from the highest occupied antibonding 2uu orbital to the low-lying unoccupied 3u, or 'nu bonding orbital will produce more strongly bonded low-lying excited states of Be2 with respect to the corresponding separated atoms. This has been deduced from spectroscopic constants and lifetime calculations for the low-lying excited states, obtained in gas phase laser induced fluorescence studies of Be2 (24)(25)(26). Similar conclusions were also arrived at in the theoretical calculations reported earlier on Be2 (3 1-33).…”
Section: Triplet States Of Bezsupporting
confidence: 71%
See 1 more Smart Citation
“…First empirical confirmation of the fact that Be 2 is a deeply bound system, as theoretically predicted, was reported in the eighties [38][39][40]. The most frequently cited experimental result for the well-depth was given by Bondybey et al, 790 ± 30 cm −1 .…”
Section: Introductionmentioning
confidence: 67%
“…A laser vaporization source requires only minor amounts of materials, permitting work with isotopically enriched samples. [29] We recently showed that full kinetic information of gas-phase reactions of cationic and anionic platinum clusters with up to 24 atoms can be obtained by using nearly pure 195 Pt. [30] This size range is vital for comparison with the reactivities of size-selectively deposited clusters on surfaces, as studied for example, by Heiz et al [31,32] When platinum cluster cations in a size range from 5 to 10 are stored in the ICR cell together with a 1:6 mixture of CO and N 2 O, for some cluster sizes sequential addition of CO is observed, while for others, a steady state between the bare platinum cluster and its oxides is established.…”
mentioning
confidence: 99%